A Molecular Analysis of Memory B Cell and Antibody Responses Against Plasmodium falciparum Merozoite Surface Protein 1 in Children and Adults From Uganda - Gonzales, S. Jake; Clarke, Kathleen N.; Batugedara, Gayani; Garza, Rolando; Braddom, Ashley E.; Reyes, Raphael A.; Ssewanyana, Isaac; Garrison, Kendra C.; Ippolito, Gregory C.; Greenhouse, Bryan; Bol, Sebastiaan; Bunnik, Evelien M. (Frontiers in Immunology, 2022)
Memory B cells (MBCs) and plasma antibodies against Plasmodium falciparum merozoite antigens are important components of the protective immune response against malaria. To gain understanding of how responses against P. falciparum develop in these two arms of the humoral immune system, we evaluated MBC and antibody responses against the most abundant merozoite antigen, merozoite surface protein 1 (MSP1), in individuals from a region in Uganda with high P. falciparum transmission. Our results showed that MSP1-specific B cells in adults with immunological protection against malaria were predominantly IgG+ classical MBCs, while children with incomplete protection mainly harbored IgM+ MSP1-specific classical MBCs. In contrast, anti-MSP1 plasma IgM reactivity was minimal in both children and adults. Instead, both groups showed high plasma IgG reactivity against MSP1, with broadening of the response against non-3D7 strains in adults. The antibodies encoded by MSP1-specific IgG+ MBCs carried high levels of amino acid substitutions and recognized relatively conserved epitopes on the highly variable MSP1 protein. Proteomics analysis of MSP1-19-specific IgG in plasma of an adult revealed a limited repertoire of anti-MSP1 antibodies, most of which were IgG1 or IgG3. Similar to MSP1-specific MBCs, anti-MSP1 IgGs had relatively high levels of amino acid substitutions and their sequences were predominantly found in classical MBCs, not atypical MBCs. Collectively, these results showed evolution of the MSP1-specific humoral immune response with cumulative P. falciparum exposure, with a shift from IgM+ to IgG+ B cell memory, diversification of B cells from germline, and stronger recognition of MSP1 variants by the plasma IgG repertoire.